Evidence-based dermatology - Ching-Chi Chi (Wolters Kluwer Medknow Publications, 2013)
Evidence-based medicine (EBM) has become a hot topic in medical practice, education, and research. However, a large number of senior doctors did not have an opportunity to learn EBM in medical schools. Firstly, this article addresses the history of EBM and the principle of practicing EBM, i.e., asking, acquiring, appraisal, application, and auditing. Secondly, this article also provides a brief introduction to evidence-based dermatology and compares the introduction of clinical practice guidelines between Europe, the UK, and the US. Finally, this article addresses the present condition and future perspective of evidence-based dermatology in Taiwan.